2020
DOI: 10.3390/horticulturae6020031
|View full text |Cite
|
Sign up to set email alerts
|

Premature Apple Fruit Drop: Associated Fungal Species and Attempted Management Solutions

Abstract: The aim of this research was to determine the incidence and possible causal pathogen(s) of premature apple fruit drop (PAFD), and also to assess some fungicides for controlling the disease organisms, in order to promote a sustainable system in orchards. The prevalence and natural incidence of apple fruit drop in cv. Anna was assessed during the 2017–2018 growing seasons in Nubaria and Cairo–Alexandria regions, Egypt. Phytopathogenic fungi were isolated from dropped fruit, and four fungicides, pyraclostrobin + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Likewise, potassium phosphates proved to be effective against phytopathogenic fungi (Arslan 2015;El-Fawy and El-Said 2018). Yet, until recently, such safe salts have not been reported as management solutions for several apple diseases in Egypt (Youssef and Roberto 2020). The inhibitory mechanisms of bicarbonates were explained in terms of hydrogen ion concentration effect of the salts which demonstrated a profound inhibitory effect on sclerotia and conidia germination of Sclerotium rolfesii and S. fuliginea, respectively (Punja and Grogan 1982;Homma et al 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, potassium phosphates proved to be effective against phytopathogenic fungi (Arslan 2015;El-Fawy and El-Said 2018). Yet, until recently, such safe salts have not been reported as management solutions for several apple diseases in Egypt (Youssef and Roberto 2020). The inhibitory mechanisms of bicarbonates were explained in terms of hydrogen ion concentration effect of the salts which demonstrated a profound inhibitory effect on sclerotia and conidia germination of Sclerotium rolfesii and S. fuliginea, respectively (Punja and Grogan 1982;Homma et al 1981).…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the susceptibility of apple fruits to different plant host isolates of B. cinerea , the number of infected lesions caused by strawberry B. cinerea and apple B. cinerea on apples treated with extracts was counted at 7 and 9 DAI, and disease incidence was calculated using the formula adjusted based on Youssef and Roberto [ 48 ]: disease incidence = (number of infected lesions/total number of assessed lesions) × 100.…”
Section: Methodsmentioning
confidence: 99%
“…This indicated that there is a huge amount of loss of production due to fruit drop, which in turn could be associated with poor handling of the plants. The common causes of fruit drop are mainly poor nutrition, diseases attack, poor tree pruning, and inaccurate irrigation [39][40][41][42] . As indicated above in Tables 5 and 6, poor nutrition, and tree management are the most common futures across the study locations.…”
Section: Fruiting and Harvestingmentioning
confidence: 99%